If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 10) + (4x + 32) = 0 Reorder the terms: (10 + 2x) + (4x + 32) = 0 Remove parenthesis around (10 + 2x) 10 + 2x + (4x + 32) = 0 Reorder the terms: 10 + 2x + (32 + 4x) = 0 Remove parenthesis around (32 + 4x) 10 + 2x + 32 + 4x = 0 Reorder the terms: 10 + 32 + 2x + 4x = 0 Combine like terms: 10 + 32 = 42 42 + 2x + 4x = 0 Combine like terms: 2x + 4x = 6x 42 + 6x = 0 Solving 42 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 6x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 6x = 0 + -42 6x = 0 + -42 Combine like terms: 0 + -42 = -42 6x = -42 Divide each side by '6'. x = -7 Simplifying x = -7
| 14+(4x)=298 | | X^2+1=10 | | 4(n+2)(n+5)=n*n*n | | 5(3a-2)+10=30 | | 12+x=2x | | 2x+10+4x+32= | | 4x+10-x=19 | | 9x^2-24x=-13 | | x^3=-52 | | 39/5/9 | | 2(3+6p)=30 | | 1(1.005)^12x=5/3 | | 3/5+22=28 | | -2*-5=x | | 3/5(1.005)^12x | | 15x+15=180 | | 4x^2+25x+47=0 | | 550000000=(b+425000)+b | | -8k=15 | | 2x+35=4x-1 | | -12*4=-32 | | 5=2(q+4)+3 | | 4(8-5h)=-8 | | 2-4(x-4)= | | -2/3v=-27 | | -2x=44 | | b/-7+1=-1 | | 8y-2=70 | | 12(z+3)=10 | | -20+8x=10x+20 | | 12(X-3)=10 | | y=x/9 |